Garaventa Evacu-trac CD7 product overview and operator training. - Garaventa (Firm) (Blaine, WA : Garaventa (Canada) Ltd.)
Provides instructions for operating the "Evacu-trac"--A device for helping evacuate physically disabled people down stairs etc. in an emergency.
Title from disc.
No Master.
Keywords: Handicapped -- Transportation; Buildings